STUDY OF β2M LEVEL IN PATIENTS WITH CHRONIC RENAL FAILURE - Al-Safar, Jenan; Al-Falahi, Yassin (Iraqi Journal of Science, 2024)
This study was carried out to demonstrate the importance of measurement of serum and urine β2M levels to confirm the clinical diagnosis of some common diseases in Iraq and Also, this work was mainly designed to study the levels in serum of patients with chronic renal failure (CRF), which they were in the end stage of renal disease (ESDR) depending on hemodialysis (HD). This study included 64 patients with CRF (ESDR/HD) comparing various serum parameters with those of 20 patients with viral infection, 6 patients with acute leukemia and 25 normal controls.A statistical difference (P<0.01) in serum levels of serum β2M was noticed between CRF patients, viral infected patients, acute leukemic patients and health controls. Mean of serum β2M levels showed of values of 24.03, 11.91 , 6.40 , 2.77 , 7.12 ,2.08 and 1.55 mg/l respectively. Serum β2M test showed a sensitivity (100% , 85% and 100%) and specificity (96%, 96% and 96% ) in patients with CRF , viral disease and acute leukemia respectively. These findings reflect the importance of β2M as differential diagnostic, prognostic parameter and tumor marker.